Hubungan Antara Dukungan Keluarga dengan Kepatuhan Minum Obat Klien dengan Halusinasi di Poliklinik Rumah Sakit Jiwa Soeharto Heerdjan Jakarta Tahun 2014 - Apriana Nona Linggu; Ice Yulia Wardani (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2014)
Family support is an attitude, action and family acceptance towards ill patients, especially patients with hallucinations. Support families who are less able to lower the patient's motivation to make health care in terms of medication adherence. This study aims to identify the relationship of family support with medication adherence in clients with hallucinations. The design of this study is the correlation with the analytic cross sectional (cross-sectional) used a sample of 100 respondents were selected by purposive sampling technique Methods (PSM). Instrument The instrument used was the modified family support from WHO and questionnaires Friedman and drug compliance of the modified Ratting Medication Adherence Scale (MARS) for the psychoses of Thompson. The results of the research study found that there is a significant relationship between family support with medication adherence. The results of this study are expected to have implications for the management of the family with the implementation of health education.